2003
DOI: 10.1007/s00332-003-0534-4
|View full text |Cite
|
Sign up to set email alerts
|

Delay Embeddings for Forced Systems. II. Stochastic Forcing

Abstract: Takens' Embedding Theorem forms the basis of virtually all approaches to the analysis of time series generated by nonlinear deterministic dynamical systems. It typically allows us to reconstruct an unknown dynamical system which gave rise to a given observed scalar time series simply by constructing a new state space out of successive values of the time series. This provides the theoretical foundation for many popular techniques, including those for the measurement of fractal dimensions and Liapunov exponents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
159
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(160 citation statements)
references
References 20 publications
1
159
0
Order By: Relevance
“…In the case of controlled discrete-time systems, in article [9], the authors investigate controlled discrete-time systems and obtain some results which are similar (but not identical) to the one presented here.…”
Section: Introductionsupporting
confidence: 56%
“…In the case of controlled discrete-time systems, in article [9], the authors investigate controlled discrete-time systems and obtain some results which are similar (but not identical) to the one presented here.…”
Section: Introductionsupporting
confidence: 56%
“…However, in the limit of large concatenation parameters, the manifold geometry and, hence, the EOFs are biased towards the most stable component of the dynamics 7 , as supported by the reduction in the number of eigenvalues above a spectral gap from five (in the manifold of raw data) to one (after concatenation); see Supplementary Information section 13. One may therefore regard the timing jitter as a form of stochastic forcing, which has been extensively studied 14 . In Supplementary Information section 3, we describe how reliable dynamical information can be obtained on timescales substantially shorter than the timing jitter.…”
mentioning
confidence: 99%
“…Although the theory discussed above applies to autonomous systems, the embedding theorem has been extended to a general class of nonautonomous systems with deterministic forcing [15], state-dependant forcing [16], and stochastic forcing [17]. For nonautonomous stationary systems, it can be shown that the delay vector needs to also include the system inputs u [17]:…”
Section: Self-organizing Rulesmentioning
confidence: 99%
“…In other words, there exists a set of inputs, from limited observations, that can represent the system dynamics. The embedding theorem has been extended to a general class of nonautonomous systems with deterministic forcing [15], state-dependant forcing [16], and stochastic forcing [17], and counts numerous applications to analysis and identification of time series [18][19][20].…”
Section: Introductionmentioning
confidence: 99%